Taiwan / The Apple of Discord in the Pacific Ocean - Chytopoulou, Eleni (Advances in Social Sciences Research Journal, 2023)
Taiwan, officially-self called the Republic of China, is an island state close to China, dominating the straits separating the North from the South China Sea (Taiwan Strait or Formosa[1] Strait). Austronesian aborigines originally inhabited the island. Chinese settled it from the opposite coast, while it was a Dutch and Portuguese colony (1624-1668). The island was recaptured in 1683 by the Chinese and remained in their possession until their defeat by the Chinese -Japanese War in 1895. The island returned to China’s sovereignty after the Second World War ended. Taiwan today is a de facto state that has claimed an autonomous course since 1949, even though until 1971, the United Nations recognized Taiwan as the representative of China. However, the People’s Republic of China has not stopped claiming it has legal sovereignty over Taiwan and the Penghu, Kinmen & Matsu Archipelago, and other smaller islands currently under Taiwan’s sovereignty and are located in the East and South China Seas. Is Taiwan a Chinese island, and should it be incorporated into China under the “One China” principle, or will it survive as an independent state with a different political and social system from the People’s Republic of China? Could U.S. support for the Taiwan regime push tensions with China over the edge?